Analisis Faktor-faktor yang Mempengaruhi Status Gizi Atlet Pencak Silat Perguruan Sisinga Berantai Al-Hikmah Kabupaten Bungo - Dwi Manna Nasami Dzakiyyah; Pudia M Indika; wilda welis; sonya nelson (Jurnal IKEOR, 2023)
The problem in this research is the factors that influence the nutritional status of the pencak silat athletes at the sisinga berantai in kabupaten bungo. This study aims to determine the factors that influence the nutritional status of pencak silat athletes in Sisinga Berantai in kabupaten bungo. The design of this research is a quantitative research with descriptive method. The subjects of this study were pencak silat athletes from the sisinga berantai of kabupaten bungo, with a sample of 18 people. The method of selecting informants used a purposive sampling method. Data collection techniques were carried out by observation, measuring indeks massa tubuh(IMT), and questionnaires. The research instrument was the researcher himself and was assisted by supporting instruments such as stationery, body scales and height using a microtoise staturmeter, questionnaire sheet, camera and mobile phone. The steps for analyzing the data are tabulating the data, presenting the data, and drawing conclusions. The results of this study indicate that the factors that affect the nutritional status of athletes are nutritional knowledge and eating habits, this can be seen from the characteristics of obese athletes obtained from measurements (IMT) and researcher questionnaires to informants. obtained 33% of the 18 Sisinga berantai pencak silat athletes kabupaten bungo in the fat category. 44% of the 18 pencak silat athletes sisinga berantai fall into the category of poor nutritional knowledge factors. 44% of 18 pencak silat athletes sisinga berantai kabupaten bungo in good Category on environmental sanitation, 33% of 18 pencak silat athletes from sisinga berantai kabupaten bungo in the good category on infectious disease factors. 50% of 18 pencak silat athletes from sisinga berantai kabupaten bungo in Moderate Category on Parents’ Income Factors. Barriers experienced by pencak silat athletes from sisinga berantai kabupaten bungo one of them is irregular eating habits and some athletes do not have access to appropriate resources such as nutrition consultants or nutritionists to help them plan the right meals and diets for their needs as athletes.